2022
DOI: 10.1002/ueg2.12352
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical bowel inflammation increases healthcare resources utilization and steroid use before diagnosis of inflammatory bowel disease

Abstract: Background: Previous data support that the inflammatory process underlying ulcerative colitis (UC) and Crohn's disease (CD) can start years before the diagnosis. The aim of this study was to determine if patients with an incidental diagnosis of UC or CD demonstrate an increase in healthcare utilization in the years preceding the symptomatic onset of the disease. Methods: We performed a multicenter, retrospective, hospital-based, case-control study. Patients with an incidental diagnosis of UC or CD during the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Recent data have shown that this pre-disease phase is also associated with a range of altered circulating markers (anti-microbial antibodies [ 25 ], anti-GM-CSF [ 26 ], anti-integrin αvβ6 [ 27 ]), serum protein signatures [ 28 30 ], fecal markers [ 31 ], increased intestinal permeability [ 32 ], proteinuria [ 33 ], and dysregulated cellular pathways [ 28 ]. In addition, subclinical disease leads to increased healthcare resource utilization and costs, especially related to Primary Care, with more prescriptions of steroids during this period [ 11 , 34 , 35 ]. Hence, it is now clear that the subclinical inflammatory process prior to disease onset has an impact on different aspects, and it is now better characterized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent data have shown that this pre-disease phase is also associated with a range of altered circulating markers (anti-microbial antibodies [ 25 ], anti-GM-CSF [ 26 ], anti-integrin αvβ6 [ 27 ]), serum protein signatures [ 28 30 ], fecal markers [ 31 ], increased intestinal permeability [ 32 ], proteinuria [ 33 ], and dysregulated cellular pathways [ 28 ]. In addition, subclinical disease leads to increased healthcare resource utilization and costs, especially related to Primary Care, with more prescriptions of steroids during this period [ 11 , 34 , 35 ]. Hence, it is now clear that the subclinical inflammatory process prior to disease onset has an impact on different aspects, and it is now better characterized.…”
Section: Discussionmentioning
confidence: 99%
“…The Basque colorectal cancer screening program invites all persons between 50 and 69 years to perform a fecal immunochemical test, followed by a complete colonoscopy in those with a positive result (cut-off 20 µg Hb/g). In this study, we included all patients with a combination of clinical, endoscopic, and histologic data, requiring the presence of chronic infiltrate and absence of any enteropathogen or alternative diagnosis, all of them suggesting a diagnosis of CD [ 18 , 19 ] and following the same criteria as in our previous reports [ 8 , 9 , 11 ]. The screening program refers all subjects with abnormal findings suggestive of inflammatory bowel disease to the Gastroenterology clinic, where alternative diagnosis is systematically ruled out.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we included all patients with a combination of clinical, endoscopic, and histologic data, requiring the presence of chronic infiltrate and absence of any enteropathogen or alternative diagnosis, all of them suggesting a diagnosis of Crohn’s disease (CD) or ulcerative colitis (UC) and following the same criteria as in previous reports from this cohort. 6 , 7 A sample containing 0.25 grams from the scalp were collected from each individual with a recent (<2 months) diagnosis of preclinical IBD. Patients receiving regular non-steroidal anti-inflammatory drugs were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported a small proportion of individuals who undergo routine bowel cancer screening colonoscopy with little or no symptomatology and are incidentally diagnosed with IBD. 5 This suggests the converse may also be true, where a subgroup of patients with an indolent disease phenotype present after having experienced a longer duration of mild symptoms.…”
Section: Letter: Fulminant Onset Complicated Inflammatory Bowel Disea...mentioning
confidence: 99%